Skandinavijos investicijų vaidmuo Latvijos žiniasklaidos reintegracijoje į Šiaurės ir Vidurio Europos žiniasklaidos modelį - Dimants, Ainārs (Information & Media, 2008)
Straipsnio tikslas – trumpai apžvelgti Latvijos žiniasklaidos privatizacijos ir koncentracijos procesus, sąlygotus užsienio investicijų. Straipsnyje nagrinėjama Skandinavijos, daugiausia Švedijos, kapitalo įtaka redakciniam autonomiškumui, naujų redakcinių instrumentų įdiegimui, siekiant žurnalistikos kokybės ir profesionalumo, o taip pat tokioms žurnalistikos struktūroms, kaip: profesinės sąjungos, žurnalistų rengimas ir mokymas bei žiniasklaidos tyrimai. Straipsnyje teigiama, jog pastarųjų metų Latvijos žiniasklaidos raidą atitinka Šiaurės/Vidurio Europos arba demokratinis-korporacinis žiniasklaidos sistemos modelis, suformuluotas mokslininkų Daniel C. Hallin ir Paolo Mancini trijų žiniasklaidos modelių ir politikos koncepcijoje. The role of Scandinavian investments for the re-integration of Latvian media in the North/Central European model of media system Ainārs Dimants Summary The aim of the paper is to give a brief overview about the development and concentration of Latvian media ownership since privatization, from the point of view of the impact of foreign investment. The paper examines the impact of Scandinavian, mainly Swedish, capital on editorial autonomy, on establishing editorial instruments to increase the quality and professionalism of journalism as well as on journalistic infrastructures such as professional unions, training and education and media research. The paper suggests that the North/Central European or Democratic Corporatist Model of media system described by Daniel C. Hallin and Paolo Mancini in their concept of three models of media and politics corresponds to the Latvian media development in the present and in the past. Key words: Latvian media system, models of media system, social history, history of communication, transparency of media ownership, investments, editorial autonomy, journalistic cultures, journalistic infrastructures, professional standards of journalism